Poverty reduction strategies : the role of health and education : a Trinidad and Tobago perspective - Theodore, Karl (PAHO WashingtonUS)
Presents an overview of the health and education sectors and looks at issues of accessibility. Highlights poverty policies and their application in health and education. Examines poverty reduction strategies. Looks at decentralization and local capacity building for poverty reduction. Presents two case studies i.e. Youth Training and Employment Partnership Programme and the School Feeding Programme.